GESTÃO AMBIENTAL DOS POSTOS REVENDEDORES DE COMBUSTÍVEIS NO ESTADO DO RIO DE JANEIRO: UMA AVALIAÇÃO CRÍTICA NA VISÃO OCUPACIONAL E AMBIENTAL DA PRESENÇA DO BENZENO NA GASOLINA AUTOMOTIVA. - Silva, Edson Ferreira da (2004)
The contamination of the environment by fuel derived from petroleum has been subject of growing research in Brazil. Such contamination can take place both trhough evaporation and accidental spills or corrosion of the underground tanks, which can cause contamination of the soil and the water table. This dissertation analized the issue of contamination by benzene present in gasoline which directly affects workers' health in the work place and places a risk to the surrounding populations. It was sougth to identify the correlations between the concentrations of benzene at the moment of filling the vehicle and the effects caused by it. It was also elaborated a pedagogical proposal to rise awareness about the risks of the exposition to Benzene. The methodology used included: 1) chemical analysis in the liquid phase of the gasoline, collected in filling stations located in the State of Rio de Janeiro; 2) semi-structured interviews with employees of the filling stations in order to identify the main complaints of occurences that take place when they handle the product; 3) evaluation of the impacts caused by benzene in the environment; and 4) critical study of technologies related to the reduction and/or removal of the levels of benzene.